2016
DOI: 10.1080/19420889.2016.1143575
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidases promote apoptosis by activating ZNRF1 ubiquitin ligase in neurons treated with an exogenously applied oxidant

Abstract: Reactive oxygen species (ROS) play an important role in causing neuronal death in a number of neurological disorders. We recently reported that ROS serve as a signal to activate neuronal apoptosis and axonal degeneration by activating ZNRF1 (zinc- and RING-finger 1), a ubiquitin ligase that targets AKT for proteasomal degradation in neurons. In the present study, we showed that the NADPH oxidase family of molecules is required for ZNRF1 activation by epidermal growth factor receptor (EGFR)-dependent phosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Mounting evidence now suggests an increase in the level of activated EGFR (p-EGFR/EGFR) in the adult brains of neurodegenerative diseases, such as AD, Parkinson's disease, and ALS, as well as brain and spinal cord injuries. This activation and upregulation of EGFR are reported in both reactive astrocytes and neurons (Liu and Neufeld, 2004;Zhang and Neufeld, 2005;Liu et al, 2006;Erschbamer et al, 2007;Li et al, 2011Li et al, , 2014Yang et al, 2011;Qu et al, 2012;Wang et al, 2012aWang et al, , 2013Kjell et al, 2014;Wakatsuki et al, 2015;Wakatsuki and Araki, 2016;Zhang et al, 2016;Chen et al, 2017).…”
Section: Egfr Expression Level and Its Role Inmentioning
confidence: 82%
See 3 more Smart Citations
“…Mounting evidence now suggests an increase in the level of activated EGFR (p-EGFR/EGFR) in the adult brains of neurodegenerative diseases, such as AD, Parkinson's disease, and ALS, as well as brain and spinal cord injuries. This activation and upregulation of EGFR are reported in both reactive astrocytes and neurons (Liu and Neufeld, 2004;Zhang and Neufeld, 2005;Liu et al, 2006;Erschbamer et al, 2007;Li et al, 2011Li et al, , 2014Yang et al, 2011;Qu et al, 2012;Wang et al, 2012aWang et al, , 2013Kjell et al, 2014;Wakatsuki et al, 2015;Wakatsuki and Araki, 2016;Zhang et al, 2016;Chen et al, 2017).…”
Section: Egfr Expression Level and Its Role Inmentioning
confidence: 82%
“…In the adult brain, injuries and pathologic conditions activate EGFR in both neurons and astrocytes (Liu and Neufeld, 2004;Zhang and Neufeld, 2005;Liu et al, 2006;Wakatsuki et al, 2015;Wakatsuki and Araki, 2016;Chen et al, 2017). This includes Huntington disease (Gu et al, 2005;Faideau et al, 2010;Abjean et al, 2018), AD (Jo et al, 2014;Ceyzériat et al, 2018), Parkinson's disease (Bandopadhyay et al, 2004;Neumann et al, 2004;Koprich et al, 2008), ALS (Kushner et al, 1991;Tripathi et al, 2017), amyloid structure formation such as a-synuclein (Chavarría et al, 2018;Duffy et al, 2018) and b-amyloid (Pike et al, 1994;Söllvander et al, 2016), and traumatic brain injuries such as weight-drop technique (Erschbamer et al, 2007;Li et al, 2011Li et al, , 2014Qu et al, 2012;Kjell et al, 2014;Shandra et al, 2019), oxygen/glucose deprivation (OGD) (Wang et al, 2012b;Liu et al, 2019), and ischemic injury (Morizawa et al, 2017;Laug et al, 2019).…”
Section: Egfr Activation In the Pathologic Adult Brainmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that proteolysis‐inducing factor (PIF) and angiotensin II induce protein degradation through the activation of NADPH oxidase in murine myotube . Wakatsuki et al reported that activated NADPH oxidase induces the activation of a ubiquitin ligase ZNRF1 (Zinc‐ and RING‐finger 1), which elicits proteasomal degradation of AKT in neurons. Other studies have shown that oxidized proteins are subjected to proteasome degradation .…”
Section: Resultsmentioning
confidence: 99%